WORKSHOP 'UI/UX DESIGN THINKING': TRANSFORMASI IDE KREATIF MENJADI PROTOTIPE APLIKASI DIGITAL BAGI GENERASI Z DI LINGKUNGAN SEKOLAH DESA PASIRJATI - Maulana Muhammad Faisal; Annisa Tsamratul"ain (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2024)
Generative Artificial Intelligence (AI) offers great potential as a learning assistant, but its use at the high school level is often suboptimal and hindered by ethical issues. This community service (PKM) activity aims to enhance the basic research skills of students in Cipondoh District through the ethical and productive use of Generative AI. The method employed was Project-Based Learning through prompt engineering workshops for research draft preparation. The results showed a 52% increase in students' ability to construct theoretical frameworks and literature reviews, and a 67% increase in understanding citation ethics. Using AI as a dialogue partner proved effective in accelerating the pre-research phase and improving students' logical thinking structures. This program recommends the need for continuous mentoring so that AI technology can become a catalyst for scientific literacy rather than a mere copy-paste tool.